In the Wake of Lombard: The Reception of Augustine in the Early Thirteenth Century - Saak, Eric Leland (Augustinian studies, 2015)
This article investigates the new attitude toward the reception and use of Augustine in the early thirteenth century as seen in the works of Helinand of Froidmont and Robert Grosseteste. Both scholars were products of the Twelfth Century Renaissance of Augustine, represented in Peter Lombard’s Sentences, the Glossa Ordinaria, and Gratian’s Decretum. Yet both Helinand and Grosseteste reconstructed Augustine’s texts for their own purposes; they did not simply use Augustine as an authority. Detailed and thorough textual analysis reveals that the early thirteenth century was a high point in Augustine’s reception, and one which effected a transformation of how Augustine’s texts were used, a fact often been obscured in the historiographical debates of the relationship between "Augustinianism" and "Aristotelianism." Moreover, in pointing to the importance of Helinand’s world chronicle, his Chronicon, this article argues for the importance of compilations as a major source for the intellectual and textual history of the high Middle Ages. Thus, the thirteenth century appears as the bridge between the Augustinian Renaissance of the Twelfth Century, and that of the Fourteenth, making clear the need for further research and highlighting the importance of the early thirteenth century for a thorough understanding of the historical reception of Augustine.